Language Processing as a Precursor to Language Change: Evidence From Icelandic - Bornkessel-Schlesewsky, Ina; Roehm, Dietmar; Mailhammer, Robert; Schlesewsky, Matthias (Frontiers in Psychology, 2020)
One of the main characteristics of human languages is that they are subject to fundamental changes over time. However, because of the long transitional periods involved, the internal dynamics of such changes are typically inaccessible. Here, we present a new approach to examining language change via its connection to language comprehension. By means of an EEG experiment on Icelandic, a prominent current example of a language in transition, we show that the neurophysiological responses of native speakers already reflect projected changes that are not yet apparent in their overt behaviour. Neurocognitive measures thus offer a means of predicting, rather than only retracing, language change.